Scaling effects of measuring disc brake airborne particulate matter emissions – A comparison of a pin-on-disc tribometer and an inertia dynamometer bench under dragging conditions. (December 2018) - Alemani, M; Wahlström, J; Matějka, V; Metinöz, I; Söderberg, A; Perricone, G; Olofsson, U
An important contributor to non-exhaust emissions in urban areas is airborne particulate matter originating from brake systems. A well-established way to test such systems in industry is to use inertia dynamometer benches; although they are quite expensive to run. Pin-on-disc tribometers, on the other hand, are relatively cheap to run, but simplify the real system. The literature indicates promising correlations between these two test stands with regard to measured airborne number distribution. Recent studies also show a strong dependency between the airborne number concentration and the disc temperature. However, a direct comparison that also takes into account temperature effects is missing. The aim of this paper is, therefore, to investigate how the transition temperature is affected by the different test scales, under dragging conditions, and the effects on total concentration and size distribution. New and used low-steel pins/pads were tested against cast iron discs/rotors on both the aforementioned test stands, appositely designed for particulate emission studies. A constant normal load and constant rotational velocity were imposed in both test stands. Results show that a transition temperature can always be identified. However, it is influenced by the test scale and the frictional pair status. Nevertheless, emissions are assessed similarly when an equivalent frictional pair status is analysed (e.g. run-in). Further investigations for fully run-in samples on the pin-on-disc should be performed in order to finally assess the possibility of using the tribometers for the initial assessment of different friction materials.